Role of simulation in open varicose veins surgery: A systematic review - Muhammad Ammar Pirzada; Nadeem Ahmed Siddiqui; Fareed Ahmed Shaikh; Shoaib Badini (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the types and effectiveness of simulators present for open varicose vein surgery. Method: The systematic review was conducted at The Aga Khan University Hospital Karachi and comprised studies published from 1st January 2000 to 30th June 2020 related to open varicose vein surgical procedures done on simulators. Databases searched were PubMed, Medline, Google Scholar, Cochrane and Scopus using appropriate key words. The primary outcome of the review was to assess the effectiveness of different types of simulators used for varicose vein surgery. Results: Of the 286 articles found, 6(2%) were included. A variety of simulators ranging from animal models, homemade simulators and commercially designed models with high fidelity options had been used. Technical competence was the major domain assessed in most of the studies 5(83.3%), while 1(16.6%) study focussed on self-assessment. Blinding was done in 4(66.6%) studies for assessment purpose, and videorecording of the trainees’ performance was done in 5(83.3%) studies. Most studies 4(66.6%) found the use of simulation to be an effective tool in achieving technical competence. Conclusion: The use of simulation in the training of surgical residents for open varicose vein surgery was found to be beneficial, but most studies were heterogeneous in terms of design, simulator types and study participants. This makes it difficult to establish the superiority of any one type of simulator over the rest. Further research is needed to develop and validate simulators in open varicose vein surgery procedures. Continuous...